A qualitative analysis of young South African perpetrators’ perceptions of their sexual offences - Khoza, Zamakhoza (My University, 2021)
South Africa has one of the highest rates of sexual violence, with rape being the most dominant form of sexual violence. Normative discourses place the adult male as the primary perpetrator of sexual violence. However, approximately over a third of sexual offences committed in South Africa are committed by young perpetrators under the age of 21. This study investigates how young sex offenders frame themselves as either accepting or rejecting normative discourses on sexual violence and their juvenile statuses. Ten young South African sex offenders, incarcerated for rape, were interviewed in juvenile correctional centres. Though all of the participants were charged with rape, the constructions of their behaviours and perceptions of self were heterogeneous. The utilisation of a post-structuralist critical discourse analysis allows for the surfacing of discourses that these young offenders used to construct their offences and themselves as offenders. Childhood and youth discourses; gendered discourses; and institutionalised discourses such as legal, educational and religious discourses, were prominent in the participants’ narratives. Hegemonic masculinity and subordinate masculinities, the construction of child, juvenile and adult constraints, as well as the intersectionality of gender, racial categories, and socio-economical levels, were junctures of negotiation for these young offenders. The participants thus both accept and reject the discourses and the constructions that frame their sexual offences in varying manners. The findings indicate that the adoption of normative discourses that frame youth as naïve allows for young sex offenders to reject their statuses as ‘sex offenders’. However, other discourses on youth delinquency simultaneously allow for self-identification as criminal adults with agency. Self-identification as a young sex offender thus finds traction at the nexus of these two contradicting subject positions. The construction of the young sex offender is thus more nuanced and layered than normative discourses may project, and this study provides alternative insights and knowledge on young sex offenders and their criminality.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Psychology to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021